2012
DOI: 10.1007/s00508-011-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of Ki-67, P53 and P63 in distinguishing partial Hydatidiform mole from hydropic abortion

Abstract: The high Ki-67 labeling index and over-expression of p53, detected by immunohistochemistry, could serve as useful adjuncts to conventional methods of diagnosis in distinguishing PHM from HA. Due to, however, the limited samples, it needs to expand the number of the cases to verify this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 8 publications
(8 reference statements)
3
14
0
Order By: Relevance
“…To explore the roles of p53 during the pathogenesis of RM, we first detected the p53 protein level in the villous tissues from 27 RM patients and paired healthy controls. We observed overexpressed p53 in the RM patients, which is in accordance with results of other researchers (Figure A,B) . Recently, lncRNAs have been identified to function as key regulators of diverse cellular processes including pregnancy .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…To explore the roles of p53 during the pathogenesis of RM, we first detected the p53 protein level in the villous tissues from 27 RM patients and paired healthy controls. We observed overexpressed p53 in the RM patients, which is in accordance with results of other researchers (Figure A,B) . Recently, lncRNAs have been identified to function as key regulators of diverse cellular processes including pregnancy .…”
Section: Resultssupporting
confidence: 92%
“…Figure 1A,B). [5][6][7][8] Recently, lncRNAs have been identified to function as key regulators of diverse cellular processes including pregnancy. 16 As a transcription factor, p53 has been found modulate the expression of many lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Other studies found the same with the conclusion that P53 can be used to differentiate between abortion and GTD and subtypes of molar pregnancy. 13,20,21 Yazaki et al, 2006 showed that there is statistically a significance difference between patients of HM, patient progress to GTN or spontaneous abortion regarding the p53 immunoexpression P <0.05. 7 Other studies had investigated other tumor suppressor protein such as P63 (which is a p53 homologue) and found -ve p63 expression in cytotrophoblasts, syncytiotrophoblasts in all cases of abortion and +ve expression in all cases of PHM and CHM.…”
Section: Figurementioning
confidence: 99%